WITHDRAWN: The Fundamental And Pathological Importance Of Oxysterol Binding Protein And Its Related Proteins. - Dye, Danielle; Bieniawski, M.; Wright, S.; McCauley, A.; Coombe, D.; Mousley, Carl (2018)
This article has been withdrawn by the authors as part of this review overlapped with the contents of Pietrangelo A and Ridgway ND. 2018. Cellular and Molecular Life Sciences. 75; 3079-98.